2008
DOI: 10.1007/s00417-008-0875-7
|View full text |Cite
|
Sign up to set email alerts
|

Side effects of commonly used glaucoma medications: comparison of tolerability, chance of discontinuation, and patient satisfaction

Abstract: Background To compare the tolerability of commonly prescribed topical glaucoma medications by determining frequency and bother of side effects, patient satisfaction with their medication, and the chance of discontinuation of eye drops. Methods The tolerability of topical glaucoma medication was studied in glaucoma patients from nine hospitals. The frequency and severity of side effects was investigated together with patient satisfaction with the medication and the probability to change medication due to report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 20 publications
(16 reference statements)
3
32
2
Order By: Relevance
“…51,52 As a result, eye drops must be given at least daily and there can be side effects from systemic delivery of the poorly absorbed drug. 53,54 This study introduced the idea of targeting the ciliary body by injection into the adjacent supraciliary space. We accessed this space, located just a few hundred micrometers below the conjunctival surface, by using a hollow microneedle designed to be just long enough to penetrate to the base of the sclera.…”
Section: Discussionmentioning
confidence: 99%
“…51,52 As a result, eye drops must be given at least daily and there can be side effects from systemic delivery of the poorly absorbed drug. 53,54 This study introduced the idea of targeting the ciliary body by injection into the adjacent supraciliary space. We accessed this space, located just a few hundred micrometers below the conjunctival surface, by using a hollow microneedle designed to be just long enough to penetrate to the base of the sclera.…”
Section: Discussionmentioning
confidence: 99%
“…Side effects of current medications were explored with two lists of 16 typical side effects from pressure-lowering eye-drops. 6 One list asked how often side effect occurred, ranging from never (0) to every day (5). The other asked how bothered the patient was by the side effect, ranging from 'not bothered' (0) to 'extremely bothered' (4).…”
Section: Data Collectionmentioning
confidence: 99%
“…A recent meta-analysis confirmed that these 2 types of glaucoma therapies produce equivalent efficacy 3. In a large study (N = 3333) of patients taking glaucoma medications, the majority (79%) reported that they were satisfied with their eye drops; however, nearly 1 in 10 patients (9%) were likely to have their medication changed at their next visit due to side effects 4. Each hypotensive agent has a characteristic side effect profile, but fixed-combination products as a group have a number of advantages over the instillation of 2 individual drugs 5.…”
Section: Introductionmentioning
confidence: 98%